A service differentiation and traffic engineering scheme for mobile ad hoc networks. (21st February 2008) - Brahma, Mohamed; Abouaissa, Abdelhafid; Lorenz, Pascal
Actually with the increasing popularity of wireless networks, which indicate that there will be a demand for communicating devices providing high capacity communication with Quality of Service (QoS), QoS becomes an important factor in wireless networks, because it offers to the network the ability to provide services to applications with some important requirements. In this paper, we describe a new approach for traffic engineering for QoS support in the wireless IEEE 802.11b. This new scheme is based on a multiple queuing system to provide service differentiation for user's flows. We investigate and analyse the performance of this approach through a set of simulations and compare its performance with the original IEEE 802.11b protocol. Using simulation results, we show the effectiveness of the proposed approach and the outperformance of the IEEE 802.11b in terms of throughput and packet loss rate.